Proteolysis Targeting Chimeras (PROTACs): A Perspective on Integral Membrane Protein Degradation - Ruffilli, Camilla; Roth, Sascha; Rodrigo, Monica; Boyd, Helen; Zelcer, Noam; Moreau, Kevin (ACS pharmacology & translational science, 2022)
Targeted protein degradation (TPD) is a promising therapeutic modality to modulate protein levels and its application promises to reduce the "undruggable" proteome. Among TPD strategies, Proteolysis TArgeting Chimera (PROTAC) technology has shown a tremendous potential with attractive advantages when compared to the inhibition of the same target. While PROTAC technology has had a significant impact in scientific research, its application to degrade integral membrane proteins (IMPs) is still in its beginnings. Among the 15 compounds having entered clinical trials by the end of 2021, only two targets are membrane-associated proteins. In this review we are discussing the potential reasons which may underlie this, and we are presenting new tools that have been recently developed to solve these limitations and to empower the use of PROTACs to target IMPs.Targeted protein degradation (TPD) is a promising therapeutic modality to modulate protein levels and its application promises to reduce the "undruggable" proteome. Among TPD strategies, Proteolysis TArgeting Chimera (PROTAC) technology has shown a tremendous potential with attractive advantages when compared to the inhibition of the same target. While PROTAC technology has had a significant impact in scientific research, its application to degrade integral membrane proteins (IMPs) is still in its beginnings. Among the 15 compounds having entered clinical trials by the end of 2021, only two targets are membrane-associated proteins. In this review we are discussing the potential reasons which may underlie this, and we are presenting new tools that have been recently developed to solve these limitations and to empower the use of PROTACs to target IMPs.